Tipologi Kepemimpinan dalam Meningkatkan Kualitas Kinerja - Khoirun Nisa'; Endah Triwisudaningsih (LP3M Universitas Islam Zainul Hasan Genggong, 2020)
Leadership basically deals with the skills, abilities, and level of influence a person has; so that he is able to influence others to jointly carry out certain activities to achieve certain goals. The difference between managers and leaders in general is that a manager only deals with objects, structures, systems and efficiency. Whereas a leader deals with effectiveness, people, empowering and channeling the potential possessed by others. An important factor that determines employee performance is leadership. Because Leadership describes the relationship between the leader and the leader & how a leader directs followers will determine how far the follower reaches the leader's goals or expectations.